GAME DEVELOPMENT PROJECT MANAGEMENT USING SCRUM FRAMEWORK: HYPERCASUAL GAME CASE STUDY 'RUSH RUNNER' - Nurjaman, Moh.; Baturohmah, Habi; Warman, Cecep (LPPM Universitas Nusa Mandiri, 2024)
The research aims to explore and implement an effective Project Management approach in Game Development using the Scrum Framework. A case study was conducted on the development of a hypercasual game titled